2021
DOI: 10.22146/ijc.60633
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvements of Bixin and Metal-Bixin Complexes Sensitized Solar Cells by 1-Methyl-3-propylimidazolium Iodide in Electrolyte System

Abstract: Bixin is one of the potential natural sensitizers used in dye-sensitized solar cells (DSSCs). In this study, bixin was complexed with Cu(II) and Zn(II) to increase its stability. The formation of the complexes was indicated by shifting peaks absorption and the changes in the fine spectral structure observed from the UV-Vis absorption spectra. The metal-bixin complex occurs due to the interaction between the ester groups of bixin and the metal. Bixin, Cu-bixin, and Zn-bixin were used separately as sensitizers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…Bixin extracts were obtained from previous work by Rahmalia et al [6]. Choline chloride (> 98%), glycerol (> 99%), ethyl acetate (> 99.5%), methanol (> 99.9%), nhexane (> 99%), calcium sulfate (CaSO…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bixin extracts were obtained from previous work by Rahmalia et al [6]. Choline chloride (> 98%), glycerol (> 99%), ethyl acetate (> 99.5%), methanol (> 99.9%), nhexane (> 99%), calcium sulfate (CaSO…”
Section: Methodsmentioning
confidence: 99%
“…Bixin has been shown to reduce the inflammatory response and atherosclerotic plaque in hypercholesterolemic rabbits [4] and prevent neuroinflammation and demyelination in mice [5]. Rahmalia et al [6][7] used bixin as a sensitizer, such as a light filter, so it has the potency to protect food products from oxidation due to light.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The stability of kaolinite-bixin organoclay increased up to 15% compared to pure bixin [8]. Another study has reported that when used as a sensitizer, the Znbixin complex can be stable up to 700 W m -2 irradiation [7]. However, most of the previous studies observed the performance of DSSC based on the maximum energy conversion efficiency parameter.…”
Section: Introductionmentioning
confidence: 97%
“…Research related to bixin as a sensitizer in DSSC proved that bixin showed better performance than norbixin [6,7]. Furthermore, incorporating bixin into the interlayer space of kaolinite can increase the stability of bixin.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have shown that the photochemical efficiency of TiO 2 can be improved by the use of sensitizers [ 53 , 54 , 55 , 56 ], including transition metal coordination complexes, such as the Cu(C 3 H 3 N 3 S 3 ) 3 complex (Cu-TTC), which was referenced in previous studies [ 57 ]. This complex formed by Cu(I) and trithiocyanuric acid (C 3 H 3 N 3 S 3 ) proved to be an effective photosensitizer in the Cu(C 3 H 3 N 3 S 3 ) 3 /ZnTiO 3 /TiO 2 (Cu/TTC/ZTO/TO) system since it allowed the insertion of e − between the conduction band of the hybrid semiconductor ZnTiO 3 /TiO 2 and the excited molecule [ 58 ].…”
Section: Introductionmentioning
confidence: 99%